Is it worth it? Interest in risky behaviors as a consequence of sensation seeking and positive affect - Butler, David Mason (Kansas State University, 2007)
Researchers have yet to examine how trait sensation seeking and state positive affect combine to influence participation in risky behaviors. This study examined how participant levels of sensation seeking and positive affect interacted to influence participant interest in performing a risky behavior. It was hypothesized that an interaction between sensation seeking and positive affect would be found, such that high sensation seekers low in positive affect would show more interest in participating in a risky activity than high sensation seekers that were high in positive affect or all participants low in sensation seeking, regardless of positive affect. Trait sensation seeking was measured in an initial group of participants (N = 693), using a subscale of the Zuckerman-Kuhlman Personality Questionnaire (Zuckerman Kuhlman, Joireman, Teta, & Kraft, 1993). Using these scores, high and low sensation seekers (N = 99) were invited to a second study, where videos were used to manipulate levels of state positive affect (Hemenover, 2003). Participants were then given a questionnaire to measure interest in participating in a risky drug study. No interaction was found, but a main effect for sensation seeking (Zuckerman, 1971) was discovered, such that high sensation seekers reported more interest in participating in a risky behavior than low sensation seekers. Therefore, it appears that participant interest in risky behaviors was a function of levels of trait sensation seeking. It is possible that problems with data collection or the risk-taking scenario contributed to the inability to support the hypothesis.
Keywords: sensation seeking; positive affect; risk taking; Psychology, Personality (0625)